EFEKTIVITAS PENDIDIKAN KESEHATAN SADARI DENGAN MEDIA PHANTOM TERHADAP PENGETAHUAN DAN PERILAKU SADARI PADA AGREGAT REMAJA - Yeni Isnaeni; Sri Setyowati; Dian Nur Adkhana Sari; Agung Rejecky (Institut Citra Internasional, 2025)
BSE (Breast Self-Examination) behavior is an effort to detect early or prevent breast cancer symptoms. One of the causes of the high incidence of breast cancer is the lack of education about breast cancer among the younger generation in early detection of breast cancer. The purpose of this study was to determine whether there is an effect of health education using phantom media on knowledge and behavior about breast self-examination (BSE) as an early detection of breast cancer in female adolescents at SMA N 5 Yogyakarta. This type of research is pre-experimental with one group pre-post test design. The population of this study was all female adolescents at SMA N 5 Yogyakarta. Respondents in this study were 30 female adolescents in grade XI. The sampling technique used was convenience sampling, namely by lottery. The instrument used was a knowledge questionnaire. The data analysis technique used the Shapiro Wilk test and the test used was the Wilcoxon test. The average knowledge score of female adolescents in grade XI of SMA N 5 Yogyakarta before being given health education using phantom media was 6.83 after being given health education using phantom media was 14.97. There was an increase in the knowledge score of 8.1. The value of the Wilcoxon test P = 0.000 (p-value = .000 < 0.05). The conclusion of the study is that there is an effect of health education using phantoms on knowledge and behavior regarding breast self-examination (SADARI) as an early detection of breast cancer in female adolescents.